13C of volatile organic compounds (VOCS) in airborne samples by thermal desorption-gas chromatography-isotope ratio-mass specrometry (TD-GC-IR-MS) - Turner, Nicole; Jones, Mark; Grice, Kliti; Dawson, Daniel; Ioppolo-Armanios, Marisa; Fisher, Steven (Pergamon, 2006)
This paper is a preliminary investigation into the use of a thermal desorption-gas chromatography-isotope ratio mass spectrometry (TD-GC-IR-MS) method to determine stable carbon isotopic compositions (d13C) of low molecular-weight volatile organic compounds (VOCs) in airborne samples (e.g. industrial and car exhaust emissions) as a means of differentiating their sources in the environment. A TD-GC-IR-MS method for obtaining d13C of VOCs (benzene, toluene,chlorobenzene, ethylbenzene, m-xylene and propylbenzene) in air samples has been optimised, and is proven to be both reproducible and linear. The d13C of the VOC standards was found to be comparable (within analytical error) to that obtained from direct GC-IR-MS analysis. This novel method of VOC analysis is valuable in environmental and forensic investigations.